2020
DOI: 10.1002/jha2.110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of anthracycline‐induced cardiotoxicity in patients with malignant lymphoma who received a CHOP regimen with or without rituximab: A single‐center, retrospective observational study

Abstract: We investigated the incidence of cardiotoxicity, its risk factors, and the clinical course of cardiac function in patients with malignant lymphoma (ML) who received a cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) regimen. Among all ML patients who received a CHOP regimen with or without rituximab from January 2008 to December 2017 in Nagoya City University hospital, 229 patients who underwent both baseline and follow‐up echocardiography and had baseline left ventricular ejection fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…Lower LVEF and smaller GLS in patients with normal LVEF were already recognized as risk factors for anthracycline-induced CTRCD. 11,13,14,18 In the current study, LVEF was not an independent determinant for anthracycline-induced CTRCD in the multivariable analysis, probably because GLS can detect myocardial injury more sensitively than LVEF. 34,35 History of ischemic heart disease is also considered a risk factor for CTRCD.…”
Section: Gls and A History Of Ischemic Heart Diseasecontrasting
confidence: 51%
See 1 more Smart Citation
“…Lower LVEF and smaller GLS in patients with normal LVEF were already recognized as risk factors for anthracycline-induced CTRCD. 11,13,14,18 In the current study, LVEF was not an independent determinant for anthracycline-induced CTRCD in the multivariable analysis, probably because GLS can detect myocardial injury more sensitively than LVEF. 34,35 History of ischemic heart disease is also considered a risk factor for CTRCD.…”
Section: Gls and A History Of Ischemic Heart Diseasecontrasting
confidence: 51%
“…Patients with LVEF < 50% at baseline but no echocardiographic images of adequate quality were excluded. The current study was the sub-analysis of a previous study in which we described the clinical features of anthracycline-induced CTRCD 18 .…”
Section: Study Populationmentioning
confidence: 99%
“…Lower LVEF and smaller GLS in patients with normal LVEF are already recognized as risk factors for anthracycline-induced CTRCD. 11,14,15, 19 In the present study, LVEF was not an independent determinant for anthracyclineinduced CTRCD in the multivariable analysis, probably because GLS can detect myocardial injury more sensitively than LVEF. 45, 46 A history of ischemic heart disease is also considered a risk factor for CTRCD.…”
Section: Gls and A History Of Ischemic Heart Diseasementioning
confidence: 55%
“…The present study is a subanalysis of a previous study in which we described the clinical features of anthracyclineinduced CTRCD. 19…”
Section: Study Populationmentioning
confidence: 99%
“…Only one patient developed Grade 3 or higher non‐hematological toxicity, which resulted in a reduction of the ejection fraction. We concluded that the cardiotoxicity was caused by R‐CHOP because it occurred prior to starting R‐BAC, and the doxorubicin contained in R‐CHOP is known to cause cardiotoxicity in a dose‐dependent manner 18,19 . One patient discontinued R‐BAC after two cycles due to a Grade 2 skin rash, which was diagnosed as eosinophilic pustulosis by a dermatologist.…”
Section: Discussionmentioning
confidence: 99%